Relationship between factor XIII activity, fibrinogen, haemostasis screening tests and postoperative bleeding in cardiopulmonary bypass surgery - Blome, Markus; Isgro, Frank; Kiessling, Arndt Holger; Skuras, Jan; Haubelt, Hannelore; Hellstern, Peter; Saggau, Werner (Thrombosis and haemostasis, 2005)
We investigated the relationship between factor XIII, fibrinogen, blood coagulation screening tests and postoperative bleeding in 98 patients undergoing cardiopulmonary bypass (CPB) surgery. All patients received aprotinin. Blood samples were collected preoperatively (T1),after termination of CPB (T2),12 h (T3) and 24 h (T4) after surgery to determine FXIII activity, fibrinogen, platelet count, prothrombin time (PT), activated partial thromboplastin time (APTT) and D-dimers (DD). Laboratory results were correlated with the chest tube drainage 24 h after surgery and compared between patients with 24-hour chest tube drain volumes in the lower (Group 1) with those in the upper tertile (Group 3). Median FXIII and fibrinogen levels dropped by 33.9% and 34.2%, respectively, during CPB. No association between FXIII activity and the extent of postoperative bleeding was found. However, chest tube bleeding was significantly correlated with preoperative and postoperative fibrinogen. This was confirmed by comparing Groups 1 and 3. Group 3 patients had significantly lower fibrinogen levels than Group 1 at T1 - T4, although most fibrinogen values were within or above the reference range (medians, g/l: 3.5 vs. 4.0, p = 0.043 at T1; 2.3 vs. 2.7, p = 0.015 at T2; 2.9 vs. 3.3, p = 0.008 at T3; 4.2 vs. 5.2, p = 0.002 at T4). There was also a significant relationship of platelet count, PT and APTT, as measured after CPB (T2), with postoperative chest tube drainage. In conclusion, plasma FXIII activity does not influence postoperative bleeding in patients undergoing CPB surgery. There is however an inverse association between preoperative or postoperative plasma fibrinogen levels and postoperative bleeding. These findings indicate a modulation of postoperative bleeding by fibrinogen levels.